The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/cncr.32597
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance imaging for patients with head and neck cancer treated with definitive radiotherapy: A partially observed Markov decision process model

Abstract: BACKGROUND: A possible surveillance model for patients with head and neck cancer (HNC) who received definitive radiotherapy was created using a partially observed Markov decision process. The goal of this model is to guide surveillance imaging policies after definitive radiotherapy. METHODS: The partially observed Markov decision process model was formulated to determine the optimal times to scan patients. Transition probabilities were computed using a data set of 1508 patients with HNC who received definitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In particular, current NCCN guidelines recommend ND if a positive PET/CT scan is associated with a lymph node dimension greater than 1 cm at the morphologic imaging 2 . In all cases with discordant imaging results, the decision to observe a watchful waiting or a surgical approach should be customized to the patient 16 . In this context, fine‐needle aspiration cytology (FNAC) of suspicious nodes represents a complementary tool.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, current NCCN guidelines recommend ND if a positive PET/CT scan is associated with a lymph node dimension greater than 1 cm at the morphologic imaging 2 . In all cases with discordant imaging results, the decision to observe a watchful waiting or a surgical approach should be customized to the patient 16 . In this context, fine‐needle aspiration cytology (FNAC) of suspicious nodes represents a complementary tool.…”
Section: Introductionmentioning
confidence: 99%
“…This finding corroborates previous studies which suggested PET/CT surveillance's cost-effectiveness for all HNC patients without stratification by HPV status. 19,26 PET/CT, with a reported NPV of 91% to 98%, [27][28][29] with clinical surveillance has been suggested as a clinically effective approach in detecting tumor recurrence among HPV +OPSCC patients 27 ; however, no comment was made on this approach's cost-effectiveness. Our decision to perform imaging surveillance at 1 year in our model is also consistent with studies that found PET/CT's predictive ability to be optimal between 3 months and 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is similar to the work by Ng et al, who developed a Markov model for HNC that was used for surveillance optimization. The same group found that imaging beyond 2 years after treatment was low yield and high cost .…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 , 20 , 21 Markov models have already been used to simulate cancer recurrence. 22 , 23 , 24 , 25 , 26 , 27 , 28 However, many models lack disease-specific risk stratification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation